Non‐invasive differentiation of non‐rejection kidney injury from acute rejection in pediatric renal transplant recipients. (4th February 2019) - Archdekin, Ben; Sharma, Atul; Gibson, Ian W.; Rush, David; Wishart, David S.; Blydt‐Hansen, Tom D.
Abstract: Acute kidney injury (AKI) is a major concern in pediatric kidney transplant recipients, where non‐alloimmune causes must be distinguished from rejection. We sought to identify a urinary metabolite signature associated with non‐rejection kidney injury (NRKI) in pediatric kidney transplant recipients. Urine samples (n = 396) from 60 pediatric transplant participants were obtained at time of kidney biopsy and quantitatively assayed for 133 metabolites by mass spectrometry. Metabolite profiles were analyzed via projection on latent structures discriminant analysis. Mixed‐effects regression identified laboratory and clinical predictors of NRKI and distinguished NRKI from T cell–mediated rejection (CMR), antibody‐mediated rejection (AMR), and mixed CMR/AMR. Urine samples (n = 199) without rejection were split into NRKI (n = 26; ΔSCr ≥25%), pre‐NRKI (n = 35; ΔSCr ≥10% and <25%), and no NRKI (n = 138; ΔSCr <10%) groups. The NRKI discriminant score (dscore) distinguished between NRKI and no NRKI (AUC = 0.86; 95% CI = 0.79‐0.94), confirmed by leave‐one‐out cross‐validation (AUC = 0.79; 95% CI = 0.68‐0.89). The NRKI dscore also distinguished between NRKI and pre‐NRKI (AUC = 0.82; 95% CI = 0.71‐0.93). In a linear mixed‐effects regression model to account for repeated measures, the NRKI dscore was independent of concurrent rejection, but there was a non‐statistical trend for higher dscores with rejection severity. A second exploratory classifier developed to distinguish NRKI from clinical rejection had similar test characteristics (AUC = 0.81, 95% CI = 0.70‐0.92, confirmed by LOOCV). This study demonstrates the potential of a urine metabolite classifier to detect NRKI in pediatric kidney transplant patients and non‐invasively discriminate NRKI from rejection.